Current and projected incidence rates of pancreatic cancer in 43 countries: an analysis of the Cancer Incidence in Five Continents database - Jie He; Yi Li; Rui Liu; Xing Zhang; Baojin Hua; Bo Pang; Songting Shou; Xiaochen Jiang; Fudong Liu; Xiyuan Zhang; Geer En; Zhiqing Pu (BMJ Open Gastroenterology)
Objective The aetiology of pancreatic cancer is complex, and there is limited research on its incidence. We aimed to investigate the incidence trends of pancreatic cancer in 43 countries and predict trends up to 2030.Methods The annual incidence of pancreatic cancer was obtained from the Cancer Incidence in Five Continents database, which comprises 108 cancer registries from 43 countries. Based on available data, we calculated age-standardized incidence rates (ASRs) per 100 000 people for 1988–2012. A Bayesian age-period-cohort model was used to predict the number of new cases and incidence rates up to 2030.Results From 1988 to 2012, the global incidence rate of pancreatic cancer showed a continuously increasing trend, with the ASR increasing from 5.89 in 1988 to 6.78 in 2012, representing an overall average annual percentage change of 8.45%. This increasing trend is expected to persist in most selected countries, whereas a few countries are projected to exhibit a declining trend by 2030.Conclusion It appears that the future global incidence of pancreatic cancer is on the rise, but the rate of increase varies among different countries, with some showing a declining trend.